Effect of weed green manure, compost manure and vermicompost on productivity of Spinach - Parbhankar RL; Mogle UP (International Journal of Life Sciences, 2017)
Organic manures were prepared from common weeds like Tephrosia and Achyranthus. Spinach seeds was sown at the seed rate 30 kg/ha, frequent irrigation was given as per requirement. In a course of time 3 regrowth’s were studied after 41, 76 and 111 days of sowing. Productivity of spinach shows maximum amount of yield produced by weed vermicompost, weed compost and green manure as compared to chemical fertilizers and control.